Awaeté-Parakanã: Awaeté Xe’enga, imopinimawaranga - Fonini Monserrat, Ruth Maria; Parakanã, Tarana; Souza Tavares, Quélvia (Revista Brasileira de Linguística Antropológica, 2024)
Awaeté-Parakanã: Awaeté Xe’enga, imopinimawaranga